Art and art history in cultural publishing of the second half of the 20th century - Irene Piazzoni (Bibliothecae.it)
The paper presents some reflections inspired by Editoria e storici dell’arte nell’Italia del secondo dopoguerra, edited by Paolo Soddu and Franca Varallo (Viella, 2024). The chapters of this book survey some episodes and figures of the process that led historiographic-artistic studies to be assimilated with cultural publishing, thus gaining a wider and more diversified audience than experts and amateurs of the “beautiful book”. At the same time, they focus on the actors (first and foremost the “intellectual-publishers” and the publishing houses), circuits, modes, and practices of the Italian cultural system around and through the lens of historiographic-artistic and figurative art-related publishing production, including books and magazines. Therefore, by placing art and art history within the framework of cultural life in the second half of the 20th century, this volume allows us to grasp aspects that contribute to enriching our knowledge.